Emissions of Perfluorinated Greenhouse Gases in Southeastern China Derived From High‐Frequency In Situ Observations - Yuyang Chen; Bo Yao; Minde An; Ao Ding; Song Liu; Xicheng Li; Yali Li; Simon O’Doherty; Paul B. Krummel; Honglong Yang; Haibo Yu; Liqu Chen; et al. (Geophysical Research Letters)
Abstract Sulfur hexafluoride (SF6), nitrogen trifluoride (NF3), and three perfluorocarbons (PFCs; CF4, C2F6, and c‐C4F8) are perfluorinated greenhouse gases (PF‐GHGs) with long atmospheric lifetimes and high global warming potentials. Using high‐frequency observations and a Bayesian inversion framework, we assess 2021–2023 PF‐GHG emissions in southeastern China, a rapidly industrializing region. Total PF‐GHG emissions rise from 69.50 (55.16–84.97) in 2021 to 96.19 (69.53–127.14) Mt CO2‐eq yr−1 in 2023, accounting for 21.74% of global total PF‐GHG emissions in 2023. NF3 emissions nearly double, reaching 0.94 (0.69–1.25) Gg yr−1, with an annual growth rate of 40.38%, likely driven by semiconductor industry expansion. SF6 (51.75%) and NF3 (30.86%) dominate 3‐year PF‐GHG growth. c‐C4F8 shows strong seasonality, with a potential winter increase linked to HCFC‐22 feedstock use. Seasonal SF6 peaks align with winter electricity demand, while C2F6 variations suggest potential links with semiconductor industry.